2015
DOI: 10.1016/j.jhep.2014.10.009
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Aldehyde dedydrogenase-2 plays a beneficial role in ameliorating chronic alcohol-induced hepatic steatosis and inflammation through regulation of autophagy

Abstract: Background & Aims Mitochondrial aldehyde dehydrogenase (ALDH2) plays a critical role in the detoxification of the ethanol metabolite acetaldehyde. This study was designed to examine the impact of global ALDH2 overexpression on alcohol-induced hepatic steatosis. Methods Wild-type friendly virus B (FVB) and ALDH2 transgenic mice were placed on a 4% alcohol or control diet for 12 weeks. Serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), bilirubin and cholesterol, hepatic triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 65 publications
4
64
1
Order By: Relevance
“…On the other hand, the lysosomal inhibitor bafilomycin A1 did not modulate the effect of EtOH on LC3B-II or SQSTM1 (data not shown). While this result is in agreement with a report examining HepG2 cells and liver from chronic alcohol-fed mice (Guo et al, 2015), it is in contrast to previous studies in myocytes where there was an additive effect of EtOH and lysosomal inhibitors (Thapaliya et al, 2014, Luo, 2014). Although there is no clear explanation for this discrepancy, it may be due to differences in cell types and/or the inhibitors used in the respective studies.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the lysosomal inhibitor bafilomycin A1 did not modulate the effect of EtOH on LC3B-II or SQSTM1 (data not shown). While this result is in agreement with a report examining HepG2 cells and liver from chronic alcohol-fed mice (Guo et al, 2015), it is in contrast to previous studies in myocytes where there was an additive effect of EtOH and lysosomal inhibitors (Thapaliya et al, 2014, Luo, 2014). Although there is no clear explanation for this discrepancy, it may be due to differences in cell types and/or the inhibitors used in the respective studies.…”
Section: Discussionsupporting
confidence: 93%
“…37,38 However, Guo et al reported that the AST/ALT ratio was significantly increased in mice fed with 4% alcohol. 39 The discrepancies in the hepatic protein levels of COI-IV and the AST/ALT ratio between previous studies and our study could be due to differences in samples, the degree of hepatic pathological damage, nutritional factors or genetic factors. Impaired mitochondrial OXPHOS complexes further decreased the mitochondrial fatty acid b-oxidation and enhanced TG accumulation.…”
Section: Discussioncontrasting
confidence: 84%
“…Nearly, half of the East‐Asian population possessed the genetic mutation which results in the deficiency of ALDH2 activity . Findings from our laboratory and others revealed a beneficial role of ALDH2 in rescuing against certain diseases, such as ischemia heart disease, alcoholic liver disease and stroke, which might be mediated through regulating oxidation stress, apoptosis and autophagy . Nevertheless, the role of ALDH2 in CCl 4 ‐induced chronic liver fibrosis and the underlying mechanisms remains to be further elucidated.…”
Section: Introductionmentioning
confidence: 81%